Unwinding of supercoiled DNA by cis- and trans-diamminedichloroplatinum(II): influence of the torsional strain on DNA unwinding. - Scovell, W M (1985)
The effective unwinding angle, phi, for cis-diamminedichloroplatinum(II) (cis-DDP) and trans-DDP was determined by utilizing high resolution gel electrophoresis and supercoiled phi X174 RF DNA as a substrate. The effective unwinding angle was calculated by equating the reduction in mobility of the DDP-modified DNA to the removal of a number of superhelical turns. The value of the effective unwinding angle for both DDP isomers was greatest at the low levels of DDP bound and decreased with increasing amounts of unwinding agent. The cis-isomer is a better unwinding agent than is the trans-isomer, being nearly twice as effective in unwinding the supercoiled DNA at the DDP levels investigated. A comparison of the magnitude of phi below rb values of 0.005 and those at high levels of binding reveals that the extent of torsional strain in the supercoiled DNA influences the magnitude of the unwinding of the DNA by these complexes. When this method is used in the analysis of the unwinding angle for a covalently bound species on supercoiled DNA, it may provide a more reliable estimate of the magnitude of phi at high degrees of supercoiling and at low levels of modification.